Component studies of psychological treatments of adult depression: A systematic review and meta-analysis - Cuijpers, Pim; Cristea, Ioana A.; Karyotaki, Eirini; Reijnders, Mirjam; Hollon, Steven D. (Psychotherapy research, 2019)
Objectives: A recent report from the US Institute of Medicine indicated that identifying core elements of psychosocial interventions is a key step in successfully bringing evidence-based psychosocial interventions into clinical practice. Component studies have the best design to examine these core elements. Earlier reviews resulted in heterogeneous sets of studies and probably missed many studies. Methods: We conducted a comprehensive search of component studies on psychotherapies for adult depression and included 16 studies with 22 comparisons. Results: Fifteen components were examined of which four were examined in more than one comparison. The pooled difference between the full treatments and treatments with one component removed was g = 0.21 (95% CI: 0.03∼0.39). One study had sufficient statistical power to detect a small effect size and found that adding emotion regulation skills increased the effects of CBT. None of the other studies had enough power to detect an effect size smaller than g = 0.55. Only one study had low risk of bias. Conclusions: The currently available component studies do not have the statistical power nor the quality to draw any meaningful conclusion about key ingredients of psychotherapies for adult depression.